Converging HRM practices? A comparison of high performance work system practices in MNC subsidiaries and domestic firms in Pakistan. Issue 5 (14th June 2019) - Ahmad, Mansoor; Allen, Matthew M.C.; Raziq, Muhammad Mustafa; ur Rehman, Wali
Abstract : Purpose: Existing work on convergence/divergence among HRM practices in MNCs and local firms mainly focuses on Europe and the USA. Limited research examines these organizations in Pakistan, hindering our understanding of what policies MNCs are likely to adopt there as well as the extent of any differences between HRM in MNC subsidiaries and local firms. The purpose of this paper is to examine the similarities and differences between the HRM practices of MNC subsidiaries and domestic firms to assess if there is evidence for convergence or divergence. Design/methodology/approach: The authors targeted MNC subsidiaries and domestically owned firms working in the banking, information technology and pharmaceutical sectors in Pakistan. These sectors have enjoyed a steady inflow of foreign direct investment and have a sizeable number of MNC subsidiaries. Out of 1, 081 companies, some 392 participated in a face-to-face survey (response rate of 36.4 percent). The authors ran a series of binary logistic regression models to test the hypothesized relationships between HR practices and nationality of ownership. Findings: The authors reveal that a small minority of both types of firm use some practices, such as high compensation contingent on performance and performance review, appraisal and career development. However, domestic firms use some practices, such as extensive training, performance appraisals and performance-related pay significantly less than their multinational counterparts. The authors argue that these differences reflect institutional influences in Pakistan as well as a potential opportunity for local firms to change their HRM practices. In other areas, such as recruitment and employee involvement, there are no differences between the two groups. Originality/value: The authors deepen our understanding of the types of HR practices that local companies in an emerging economy are likely to adopt as well as those that they are unlikely to adopt. Existing research has tended to downplay HRM in Pakistan and the different use of individual HRM practices among MNC subsidiaries and local firms. This research reveals that some companies in Pakistan have sophisticated HRM practices in place in some areas; however, MNC subsidiaries make greater use of some HR practices, reflecting different cultural norms between the two groups.